Exploration Community Empowerment of Lumajang Typical Batik Enterprises for Culture Preservation - Joko Setiyo; Ratna Daniar Paramita; Riza Bahtiar Sulistyan (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This study aims to explore the existing batik culture in Lumajang district and to find out the obstacles faced during the production process. Design/methodology/approach: This research uses a qualitative approach. The data collection method used interviews, observations, and documentation which were carried out in the batik-producing area in Lumajang Regency Findings: The results showed that batik entrepreneurs in Lumajang district, apart from preserving culture, were also used to improve the economy of the surrounding community. The batik culture is in the form of regional motifs such as the batik motif of the great banana, sand, and semeru mountain which are applied to the cloth with the batik process which will later be used as uniforms for the Lumajang Regency Government. Increasing the capacity of batik craftsmen also needs improvement through training activities. Research limitations/implications: This research is limited to cases that exist in batik craftsmen in Lumajang district. Practical implications: This research can be used as input for interested parties to increase batik production. In addition, it can also increase the sense of belonging to the culture around us.. Originality/value: This paper is original Paper type: Research paper